Diagnosed diabetes and optimal disease control of prisoners in Catalonia - M Pagarolas-Soler; P Alonso-Gaitón; N Sapera-Miquel; J Valiente-Soler; M Sánchez-Roig; A Coll-Cámara
ABSTRACT Objectives: To determine the prevalence of diagnosed diabetes (DD) and its control amongst prisoners in Catalonia. Materials and methods: Transversal study carried out in four Catalan prisons between April and May 2016. The prevalence of DD in inmates was calculated by intentional sampling and collecting the following variables about: a) type of diabetes, value of glycosylated hemoglobin (HbA1c) and treatment; b) comorbidities; c) epidemiological and prison variables; knowledge of hyperglycaemia/hypoglycaemia, and e) participation in educational activities. Optimal control was considered to exist if Hb1A<7.5% and high risk if Hb1Ac >9%. Test x2 was used in order to study the association among qualitative variables. Multivariate analysis was carried out using logistic regression to determine variables associated with disease control. Results: The study group considered 4,307 male patients, 50.2 years of average age. Ninety-three cases of DD were detected (prevalence 2.16%). 22.6% were treated with insulin, 51.6% with oral antidiabetics (OAD) and 25.8% with both. Type 1 users were younger, thinner, diagnosed at a younger age, heavy drug users and acknowledged to know how to act in the event of hyperglycaemia/hypoglycaemia. Optimal control was more common in type 2 diabetics, but multivariate analysis only associated it with OAD treatment. Discussion: The prevalence observed in DD is much lower than that of the population outside prison and may be underestimated. Optimal control is low, and risk is very high, the results may be biased by the type of population, frequently drug-dependent and with few healthy habits. It is recommended to implement diabetes programmes or improve existing ones in order to increase the diagnosis and management of the disease.